Socio-economic Determinants of Maternal Healthcare Behaviour: Evidence from Pakistan - Sadaf Munir Ahmed; Asma Hyder (NUST Journal of Social Sciences and Humanities, 2021)
Maternal healthcare behaviour is a complex behavioural phenomenon. Studies refer to maternal healthcare behaviour as a determinant of individual, household and social factors such as accessibility, affordability and awareness regarding health care. Using the Pakistan Demographic and Household Survey, 2012-13, the study aims to identify the socio-economic determinants of maternal healthcare behaviour of women in Pakistan. Women’s health is a neglected area of study in Pakistan; particularly at household level thus this study will provide an insight into this sensitive area. Empirical estimation is carried out through simple econometric procedure. The econometric specifications followed in the study identify the potential variables that could influence pre and postnatal healthcare behaviour of women in Pakistan. The estimates of this analysis depict that mother’s predisposing factors such as educational level, previous fetal loss experience; spousal educational attainment and economic status are important determinants of maternal health behaviour (MHB) in Pakistan.